2020
DOI: 10.3390/s20154185
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Auxetic Textured Soft Strain Gauge for Monitoring Animal Skin

Abstract: Recent advances in hyperelastic materials and self-sensing sensor designs have enabled the creation of dense compliant sensor networks for the cost-effective monitoring of structures. The authors have proposed a sensing skin based on soft polymer composites by developing soft elastomeric capacitor (SEC) technology that transduces geometric variations into a measurable change in capacitance. A limitation of the technology is in its low gauge factor and lack of sensing directionality. In this paper, we propose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Based on results from prior work evaluating the performance of various non-auxetic 19 and auxetic 20 textures, four candidate corrugated patterns are selected: a symmetric diagonal grid, a diagrid, a reinforced diagrid, and a non-symmetric re-entrant hexagonal honeycomb pattern. The diagonal grid (Figure 2(a)) is selected because of its fabrication simplicity.…”
Section: Selected Corrugated Patternsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on results from prior work evaluating the performance of various non-auxetic 19 and auxetic 20 textures, four candidate corrugated patterns are selected: a symmetric diagonal grid, a diagrid, a reinforced diagrid, and a non-symmetric re-entrant hexagonal honeycomb pattern. The diagonal grid (Figure 2(a)) is selected because of its fabrication simplicity.…”
Section: Selected Corrugated Patternsmentioning
confidence: 99%
“…The re-entrant hexagonal honeycomb pattern (Figure 2(d)) is an auxetic pattern, selected because it exhibited best performance among other auxetic patterns in. 20 Each corrugated pattern forms the top-surface texture of the sensing film with a sensing area of 63.5 mm by 63.5 mm (2.5 in by 2.5 in). The untextured pattern (flat pattern) used in prior work 9 is also considered in the evaluation for benchmarking purposes.…”
Section: Selected Corrugated Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…Metamaterials are used to augment materials with additional functionalities including energy absorption, sensitivity, stretchability, and negative Poisson's ratio (NPR) [16]. Recently, auxetic metamaterials with NPR have been employed as conversion media in lieu of natural materials for developing high-performance PEH [17] and sensors [18]. In one of the initial works on metamaterial-inspired PEH, Farhangdoust et al [17] have analytically and numerically demonstrated that the harvested power output of a kirigami auxetic type of PEH could be 19.2 times greater than the power output produced by an equivalent conventional PEH.…”
Section: Introductionmentioning
confidence: 99%